Comparative Fatty Acid Compositions of Tissues of Rainbow Trout (Oncorhynchus mykiss) with Different Ploidy and Sex - Birol Baki; Dilara Kaya Öztürk (Turkish Journal of Agriculture: Food Science and Technology)
The purpose of this study was to evaluate the fatty acid contents in various tissues (fillet, liver, gonad) of different ploidy (triploid and diploid) and sex (female and male) rainbow trout (Oncorhynchus mykiss) in the breeding season. In the study, diploid and triploid rainbow trouts belonging to the same age group (3+) were used. Fish were fed with commercial feed containing 45% crude protein and 20% crude fat until satiation. At the end of the 75-day study, biometric measurements of the fish were made and the tissues were stored in a deep freezer until biochemical and fatty acid analysis. The first finding of this study identified that ploidy (triploid and diploid) affects the biochemical and fatty acid composition of rainbow trout. The second major finding was that the polyunsaturated fatty acid values were higher and the saturated fatty acid values were lower in all tissues (especially female gonads) than other fatty acids. The results also indicate that the comparative among the biochemical and fatty acid composition of the fillet, liver, and gonad of rainbow trout is further illuminated by these data.